C-H center dot center dot center dot N hydrogen bonds mediated solid state structures of 2,2 `-bis (4-pyridylsulfanylmethyl)-1,1 `-biphenyl and 9-(4-pyridylsulfanyl)phenanthrene - Upadhye, Ketaki; PrakashaReddy, J.; Pedireddi, V. R. (Journal of Molecular Structure, 2009)
Solid state structure elucidation of sulfanyl ligands, 2,2'-bis(4-pyridylsulfany[methyl)-1,1'-biphenyl, L(1) and 9-(4-pyridylsulfanyl)plienanthrene, L(2) are reported. In the structures L(1) and L(2), the molecules are self-assembled through C-H center dot center dot center dot N hydrogen bonds, yielding ensembles of cyclic and helical networks. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonds; noncovalent interactions; Supramolecular assemblies